THE INFLUENCE OF WORK DISCIPLINE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. WISMA SERATUS SEJAHTERA - Hossam, Akhmad Rafli; Haryoto, Cecep (UNIVERSITAS PAKUAN, 2025)
This study aims to test and analyze the influence of Work Discipline and Organizational Culture on Employee Performance at PT. Wisma Seraus Sejahtera. The independent variables used are Work Discipline and Organizational Culture, while the dependent variable is Employee Performance. The data collection method in this study was carried out by distributing questionnaires to 38 respondents at PT. Wisma Seratus Sejahtera. The research method used is a quantitative method that is associative using primary data. These results indicate that Work Discipline has a positive and significant effect on Employee Performance with a calculated t value greater than t table 2.232> 2.030 and a significant value of 0.032 2.030 and a significant value of 0.004 3.27 and a significant value of 0.001 < 0.05.